Study on the Meshing Characteristic of Quadruple-arc Spiral Bevel Gear - Ren Zhongyi; Zhao Qinghua; Duan Jianzhong; Jiang Biqiong (Jixie chuandong)
The quadruple-arc spiral bevel gear is a new type of spiral bevel gear which is obtained by apply the quadruple-arc tooth on the bevel gear. The meshing points of quadruple-arc spiral bevel gear are increased compare with double-arc spiral bevel gear,and the carry capacity is also increased. The mesh line figure is obtained by analyzing the cutting process of quadruple-arc spiral bevel gear,the multi-meshing points coefficient and multi-meshing teeth coefficient are calculated. The basis of calculation for the strength calculation and dimensions design of quadruple-arc spiral bevel gear is provided.